Implementasi Kebijakan Merdeka Belajar Dalam Meningkatkan Kompetensi Siswa - Magdalena; Winarti; Yulianti (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2022)
This study aims to provide an overview of the implementation of independent learning policies in improving student competence. The research method used is library research, namely journal articles, proceedings, research reports and so on. Independent learning is a policy that aims to create freedom and independence for students and teachers in the learning process. The results of this study are (1) independent learning includes 4 important points, namely changing the national exam to a minimum competency assessment, the provision of national standard school exams carried out entirely by schools, simplification of learning implementation plans, and the existence of a zoning system. (2) the problems of independent learning include the lack of teacher ability in conceptualizing and implementing independent learning (3) the need for innovation in student-centered learning models, developing teacher qualifications, and collaboration between educators and education staff. Freedom to learn helps students and teachers to be independent in thinking, imitating, independent, creative and independent for happiness.